2022
DOI: 10.1021/acsomega.2c05399
|View full text |Cite
|
Sign up to set email alerts
|

Facile Microwave Synthesis of Hierarchical Porous Copper Oxide and Its Catalytic Activity and Kinetics for Carbon Monoxide Oxidation

Abstract: The synthesis of copper oxide (CuO)-based nanomaterials has received a tremendous deal of interest in recent years. Particularly, the design and development of novel CuO structures with improved physical and chemical properties have attracted immense attention, especially for catalysis applications. We report on a rational, rapid, and surfactant-free microwave synthesis (MWS) of hierarchical porous copper oxide (HP-CuO) with a three-dimensional (3D) sponge-like topology using an MWS reactor. The activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Their work particularly emphasized the synthesis of ceria-reduced graphene oxide composites, which exhibited exceptional performance in CO oxidation, surpassing that of stand-alone materials. Another notable advancement was presented by Zedan et al in their exploration of copper oxide (CuO)-based nanomaterials . They demonstrated a unique microwave synthesis approach that yielded hierarchically porous copper oxide with enhanced catalytic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work particularly emphasized the synthesis of ceria-reduced graphene oxide composites, which exhibited exceptional performance in CO oxidation, surpassing that of stand-alone materials. Another notable advancement was presented by Zedan et al in their exploration of copper oxide (CuO)-based nanomaterials . They demonstrated a unique microwave synthesis approach that yielded hierarchically porous copper oxide with enhanced catalytic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Another notable advancement was presented by Zedan et al in their exploration of copper oxide (CuO)-based nanomaterials. 33 They demonstrated a unique microwave synthesis approach that yielded hierarchically porous copper oxide with enhanced catalytic properties. These materials showed superior performance in CO oxidation compared with conventionally synthesized CuO.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Zedan et al. synthesized a new type of 3D spongy porous CuO by a microwave method, which has large porosity and specific surface area, high thermal stability and reducibility . Their work demonstrated that this particular structure has a significant positive effect on catalytic activity.…”
Section: Synthesis Of Cu-based Semiconductor Nanomaterialsmentioning
confidence: 99%
“…Also, CO is one of the undesired and deteriorating impurity gases that can poison catalysts used in some technological applications such as polymer electrolyte membrane fuel cells even at trace levels [4]. Therefore, technological approaches have been introduced for the elimination of CO via direct capture using CO fixation materials [5], electrocatalytic oxidation [6], photocatalytic oxidation [7], and thermochemical catalytic oxidation into carbon dioxide (CO 2 ) [8,9]. The thermochemical catalytic oxidation of highly toxic CO into less toxic CO 2 by using a heterogeneous catalyst is an efficient and reliable technique for the continuous removal of CO in the gas phase [10].…”
Section: Introductionmentioning
confidence: 99%